α-Interferon therapy for HBV-related glomerulonephritis - Lopes Neto, Edmundo Pessoa de Almeida (1998)
We report a case of a patient with hepatitis B virus (HBV)-related membranous glomerulonephritis (MGN) who showed improvement after interferon-α therapy. A 35-year-old man with nephrotic syndrome and HBV antigens received a 24-week course of IFN-α At the end of therapy there was an elevation in the level of plasma aminotransferase and an increase in proteinuria, which were followed by antigen/antibody seroconversion. This "flare-up" before seroconversion suggests an increase in disease activity in the liver and kidney, demonstrating in vivo HBV involvement in MGN.